Design, synthesis, and biological evaluation of novel halogenated chlorido[N,N′-bis(salicylidene)-1,2-bis(3-methoxyphenyl)ethylenediamine]iron(III) complexes as anticancer agents - Astrid Dagmar Bernkop-Schnürch; Klaus Huber; Armida Clauser; Monika Cziferszky; Daniel Leitner; Heribert Talasz; Martin Hermann; Stephan Hohloch; Ronald Gust; Brigitte Kircher (JBIC Journal of Biological Inorganic Chemistry, 2024)
Iron(III) complexes based on N,N ´-bis(salicylidene)ethylenediamine (salene) scaffolds have demonstrated promising anticancer features like induction of ferroptosis, an iron dependent cell death. Since poor cellular uptake limits their therapeutical potential, this study aimed to enhance the lipophilic character of chlorido[ N,N ′-bis(salicylidene)-1,2-bis(3-methoxyphenyl)ethylenediamine]iron(III) complexes by introducing lipophilicity improving ligands such as fluorine ( X1 ), chlorine ( X2 ) and bromine ( X3 ) in 5-position in the salicylidene moieties. After detailed characterization the binding to nucleophiles, logP values and cellular uptake were determined. The complexes were further evaluated regarding their biological activity on MDA-MB 231 mammary carcinoma, the non-tumorous SV-80 fibroblast, HS-5 stroma and MCF-10A mammary gland cell lines. Stability of the complexes in aqueous and biological environments was proven by the lack of interactions with amino acids and glutathione. Cellular uptake was positively correlated with the logP values, indicating that higher lipophilicity enhanced cellular uptake. The complexes induced strong antiproliferative and antimetabolic effects on MDA-MB 231 cells, but were inactive on all non-malignant cells tested. Generation of mitochondrial reactive oxygen species, increase of lipid peroxidation and induction of both ferroptosis and necroptosis were identified as mechanisms of action. In conclusion, halogenation of chlorido[ N,N ′-bis(salicylidene)-1,2-bis(3-methoxyphenyl)ethylenediamine]iron(III) complexes raises their lipophilic character resulting in improved cellular uptake. Graphical abstract